Impact on the use of traditional fishing practices in the coastal strip from Bilwi - Downs Coleman, Carlos; Dino Steven, Kaleth Robert (Revista Universitaria del Caribe, 2019)
The present study deals with the impact generated by the use of fishing practices in the coastal areas from El Muelle neighborhood and El Cocal community, in Bilwi City. Traditional fishing has become the most important livelihood for families that have inhabited the coastal strip of Bilwi. With the passing of time the fishing practice began to innovate or improve, with the obtaining of new materials and new forms of construction for greater use of the resource causing damage to the seabed and marine species, causing also negative impact on marine ecosystems and habitats. With this research, the impact caused by the use of fishing gear, the importance and the benefit it generates in terms of the knowledge acquired by artisanal fishermen is concisely identified. The research study is qualitative at a descriptive level. It is based on observations of fishing activities carried out by fishermen, exploration of the work area where they carry out their fishing activities and with the types of fishing practices with which they catch. The problems encountered in the area are described concisely, according to the objectives of the investigation. The information to carry out this study was obtained through documents and investigations carried out by intellectuals, interviews with neighborhood authorities and fishermen. The data indicates that both the fishing population and the fishing effort have been increasing, creating unfavorable conditions such as the extinction of species.